The ACE2 Receptor from Common Vampire Bat (Desmodus rotundus) and Pallid Bat (Antrozous pallidus) Support Attachment and Limited Infection of SARS-CoV-2 Viruses in Cell Culture - Abhijeet Bakre; Ryan Sweeney; Edna Espinoza; David L. Suarez; Darrell R. Kapczynski (Viruses)
During the COVID-19 pandemic, severe acute respiratory syndrome coronavirus 2 (SC2) infection was confirmed in various animal species demonstrating a wide host range of the virus. Prior studies have shown that the ACE2 protein is the primary receptor used by the virus to gain cellular entry and begin the replication cycle. In previous studies, we demonstrated that human and various bat ACE2 proteins can be utilized by SC2 viruses for entry. Bats are a suspected natural host of SC2 because of genetic homology with other bat coronaviruses. In this work, we demonstrate that expression of ACE2 genes from the common vampire bat (CVB) (Desmodus rotundus) and the pallid bat (PB) (Antrozous pallidus), supports infection and replication of some SC2 viruses in cell culture. Two cell lines were produced, CVB-ACE2 and PB-ACE2, expressing ACE2 from these bat species along with human TMPRSS2, in a model previously established using a non-permissive chicken DF-1 cell line. Results demonstrate that the original Wuhan lineage (WA1) virus and the Delta variant were able to infect and replicate in either of the bat ACE2 cell lines. In contrast, the Lambda and Omicron variant viruses infected both cell lines, but viral titers did not increase following infection. Viral detection using immunofluorescence demonstrated abundant spike (S) protein staining for the WA1 and Delta variants but little signal for the Lambda and Omicron variants. These studies demonstrate that while ACE2 from CVB and PB can be utilized by SC2 viruses to gain entry for infection, later variants (Lambda and Omicron) replicate poorly in these cell lines. These observations suggest more efficient human adaption in later SC2 variants that become less fit for replication in other animal species.